Surface Temperature Distribution on Aluminum Hollow Heated Using Two Pairs of Thermoelectric. Issue 1 (June 2021) - Putro, T; Triqadafi, A O; Sakti, S P
Abstract: In the development of a gas sensor using Quartz Crystal Microbalance (QCM), the temperature of the headspace needs to be controlled. In this work, the temperature distribution of the aluminum hollow as a headspace was observed using a thermal imaging camera. In addition, the heating rate was also measured. The aluminum hollow was a square hollow with a dimension of 40mm x 40mm with a length of 20cm. The hollow thickness was 1 mm. The aluminum is heated using two pairs of thermoelectric that are mounted opposite each other. The aluminum surface temperature was set at 70 ° C and observed using the Fluke TiS20 thermal imaging camera. We found that the temperature distribution on the surface in the adjacent direction to the thermoelectric surface was evenly distributed with a temperature difference of 1°C. In the parallel direction, the temperature difference of 1°C existed in a length of 33.3 mm. It suggests that placement of the sensor with a temperature difference of less than 1°C can be varied in an area of 40mmx33.3mm.